Isolation and Characterization of Lactic Acid Bacteria from Fermented Goat Milk in Tajikistan - Cho, Gyu-Sung; Cappello, Claudia; Schrader, Katrin; Fagbemigum, Olakunle; Oguntoyinbo, Folarin A.; Csovcsics, Claudia; R ö sch, Niels; Kabisch, Jan; Neve, Horst; Bockelmann, Wilhelm; Briviba, Karlis; Modesto, Monica; et al. (Journal of microbiology and biotechnology, 2018)
The lactobacilli associated with a fermented goat milk product from Tajikistan were isolated to characterize their technological properties and antibiotic resistances in order to assess their suitability for development as starter cultures. In this study, twenty three strains were identified by 16S rRNA sequencing as typical dairy-associated lactic acid bacterial strains, , , , and . These strains were generally susceptible to most antibiotics tested in this study and this allowed a selection of strains as safe starters. The draft genomes of four representative strains were sequenced and the number of contigs of the four assembled genomes ranged from 51 to 245 and the genome sizes ranged from 1.75 to 3.24 Mbp. These representative strains showed differences in their growth behavior and pH-reducing abilities in studies. The co-inoculation of these spp. strains together with a yeast MBT-5698, or together with the yeast and an additional MBT-2, led to a pH reduction to 3.4 after 48 h. Only in the case of fermentation inoculated with the co-culture, the viscosity of the milk increased noticeably. In contrast, fermentations with single strains did not lead to gelation of the milk or to a decrease in the pH after 24h. The results of this study provide a comprehensive understanding of the predominant lactobacilli related to Tajikistani fermented milk products.